The consistency of Federalist Society-affiliated U.S. supreme court justices - Tim Komatsu; Paul M. Collins (PLoS ONE, 2025)
The U.S. Supreme Court has recently undergone a dramatic turn to the right, fundamentally reshaping law and politics in America. In this article, we examine one reason for this shift: the increasingly prominent role of the Federalist Society in the conservative legal movement. An analysis of almost 25,000 votes of Supreme Court justices from 1986–2022 shows that justices affiliated with the Federalist Society are about 10 percentage points more likely to cast a conservative vote than their non-affiliated counterparts, and the voting behavior of Federalist Society-affiliates is more ideologically consistent than non-affiliated justices. Because justices in the contemporary era serve on the Court for an average of about a quarter century, these findings indicate that we are likely to see the Court’s conservative justices – who are all Federalist Society-affiliates – continue to advance the conservative legal movement’s agenda for decades to come.